Analisis Kekuatan Massa Batugamping Dengan Menggunakan Kaidah Hoek-Brown Failure Criterion-Roclab di Daerah Gunung Sudo Kabupaten Gunung Kidul Yogyakarta - Wijaya, R. Andy Erwin; Isnawan, Dianto (PROMINE, 2015)
The research area is a limestone quarry region prospect, located in Gunung Sudo, Gunung Kidul Regency, Special Region of Yogyakarta Province. Safety factor of bench in limestone quarry is extremely determined by rock mass quality. The aim of this research is analyzing of rock mass strength of limestone in the quarry prospect using the Hoek-Brown failure criterion.     The research used quantitative method. To obtain rock mass strength analysis of limestone needs some parameters. The main parameters are uniaxial compressive strength of intact rock, GSI, lithology, disturbance factor, unit weight and application for slope (height).To solve this analysis is assisted by Roclab software. The Roclab is a software program for determining rock mass strength parameters based on the generalized Hoek-Brown failure criterion.     Final result of the research will be used for safely mine design of the limestone quarry.  Keywords: Rock mass strength, Limestone, Roclab.